Islamic Leadership Inventory For Organizations - Mahazan Abdul Mutalib @ Talib; Mizan Adiliah, A.I.; Wan Mohd Fazrul Azdi Wan Razali; Nurhafizah, S.; Mohd. Zainol, A.A.; Salhah, A.; Amin Al-Hadi, S.; Saedah, A.G.; Abdul Halim, H (AENSI Publisher, 2024)
Non-Indexed Publication